Reliability and validity of the Chinese version of a short form of the family health scale - Wang, Fei; Wu, Yunchou; Sun, Xiaonan; Wang, Dong; Ming, Wai-Kit; Sun, Xinying; Wu, Yibo (BMC family practice, 2022)
With the release of the Health China Action (2019-2030), family health is receiving increasing attention from experts and scholars. But at present, there is no family health scale in China that involves multidimensional and interdisciplinary commonality. To translate a Short Form of the Family Health Scale (FHS-SF) and to test the reliability and validity of the Chinese version of the FHS-SF. A Short Form of the Family Health Scale was Chinese translated with the consent of the original author. A total of 8912 residents were surveyed in 120 cities across China using a multistage sampling method, with gender, ethnicity, and education level as quota variables. Seven hundred fifty participants were selected to participate in this study, and 44 participants were randomly selected to be retested 1 month later. The Cronbach's alpha of the Chinese version of a Short Form the Family Health Scale was 0.83,the Cronbach's alphas of the four subscales ranged from 0.70 to 0.90, the retest reliability of the scale was 0.75, the standardized factor loadings of the validation factor analysis were above 0.50, GFI = 0.98; NFI = 0.97; RFI = 0.95; RMSEA = 0.07, all within acceptable limits. The Chinese version of a Short Form the Family Health Scale has good reliability and validity and can be used to assess the level of family health of Chinese residents.